Wayang potehi: Glove puppets in the expression of Sino-Indonesian identity. (14th September 2015) - Stenberg, Josh
Abstract : This article examines wayang potehi, a cloth glove puppet theatre of southern Fujian origin performed on Java. It outlines the genre's emergence in Fujian, its arrival in the archipelago, and historical and contemporary practice. This article seeks to respect potehi's Hokkien roots, Indonesian practice, and the place of its genre in a dynamic regional history as it traces the development, practice and uses of the genre. Contemporary potehi patronage often exhibits the strategies of the mixed-culture non-Chinese-speaking communities of East and Central Java to perform a streamlined, integrationist, and loyal Sino-Indonesian identity.